Analysis of Arabic Semester Final Examination Items: Statistical and Educational Approaches in Foreign Language Institutions (LPBA) - Mohammad Sofi Anwar; Durrotus Tsaminah; Hilman Sholehuddin; Nur Qomari (Kitaba, 2023)
This study analyzed the grains of Arabic for the final assessment of the semester in the Pantoktan Pesantren Al Yasini Pasuruan. The grain of analysis is called a double option amounts to 50 items. This analysis aims to know the characteristics of good tests based on validity, differentness, casting rate, and difficulty level. This research is quantitative research whose data analysis is presented in descriptive. The result of the item grains is said to be 100% valid and divided into three easy, moderate, and difficult categories. In addition, the letters of Arabic are also analyzed by the power to know the difference in leaf ability, so obtained five categories are ugly, enough, well, very good, and inappropriate. In addition to analyzing the matter, this study also analyzed the pattern of answers as a castled rate that the result of 144 options may be loaded and the remaining six may not